The Influence of Entrepreneurial Psychological Leadership Style on Organizational Learning Ability and Organizational Performance - Tong, Yixu (Frontiers in Psychology, 2020)
In order to study the influence of different entrepreneurial psychological leadership styles on organizational learning ability and organizational performance and to provide theoretical basis for the improvement of organizational benefits of entrepreneurial enterprises in the future, 421 general managers, middle managers, and grassroots managers of 350 small- and medium-sized private enterprises in Beijing were surveyed by questionnaire in two forms: online and on-site. Then, a hypothesis model of the relationship between different entrepreneurial psychological leadership styles and organizational learning ability and organizational performance was constructed. The correlation between transformational, transactional, and laissez-faire psychological leadership styles and organizational performance and organizational learning ability was analyzed using multiple regression models. AMOS 7.0 software was used to simulate and verify the model. The results show that transformational psychological leadership style is positively correlated with organizational learning ability, financial performance, and growth performance; transactional psychological leadership style is positively correlated with organizational financial performance, growth performance, and organizational learning ability; there is no correlation between laissez-faire psychological leadership style and organizational financial performance and growth performance, but there is a significant positive correlation between laissez-faire psychological leadership style and organizational learning ability. The covariance between the error terms of the internal and external potential variables of the model is positive, and the factor load value of each potential variable and the observed variable is between 0.5 and 1, which shows that transformational and transactional psychological leadership styles have a more positive influence on organizational financial performance and learning ability than a laissez-faire psychological leadership style. The hypothesis model of the relationship between entrepreneurial psychological leadership styles and organizational learning ability and organizational performance conforms to the adaptation criteria and is feasible.